First description of the male of the millipede Eurygyrus euboeus (Verhoeff, 1901) (Diplopoda: Callipodida: Schizopetalidae) - Stoev, Pavel (Zootaxa, 2007)
The external morphology and the shape of gonopods of the male of Eurygyrus euboeus (Verhoeff, 1901), a species hitherto known only from a single female specimen collected more than 100 years ago on the Greek island of Euboea, is documented for the first time. The structure of gonopods indicates that the species belongs to the E. xanthinus group, and is closely related to the Anatolian species E. ochraceus C.L. Koch, 1847. The new find extends the species’ range ca. 60 km in a northwestern direction.